Gas Station Competitive Intensity in Jakarta: A Customer Perspective - Fatonny, Ardicho Rahman; Aprianingsih, Atik (Journal of Business and Management, 2014)
The competition of vehicle fuel retail industry will rise due to Indonesian government’s plan to reduce fuel subsidy. The plans are to allow the consumption of subsidized fuel only for the actual subsidy target. Currently, those who do not belong to subsidy target are still allowed to consume the subsidized fuel. This can be seen that seventy-seven percent (77%) of subsidized vehicle fuel are consumed by the middle-high class. When the plan is implemented, the middle-high class who used to consume subsidized target due to the price will have to consume non-subsidized fuel. They will have wider option since Pertamina is not the only company that sells non-subsidized fuel. Therefore, Pertamina will face a tighter competition with Shell and Total. Thus, Pertamina has to set strategy to win the future competition. This research has purpose to investigate the consumer perception toward three gas station companies in Jakarta, which are Pertamina, Shell, and Total. The methods used are gap analysis and multidimensional scaling (MDS) which is then used to build a perceptual map. The population is the amount of personal car in Jakarta, which is 2,742,414. The minimum sampling size is 100 people and the author took sample of 125. For data collecting, the author used questionnaire that consist of questions about each gas station performance toward several attributes, which are extracted from the 7P marketing mix. The result shows that Pertamina has strong perception on fuel price, access, facilities, accuracy, and advertising attributes. Shell has a strong perception on capacity, sales program, personnel appearance, personnel performance, and comfort attributes. Total has strong perception on fuel quality and cleanness attributes. Pertamina need to do some improvement on the attributes that belong to preferred attribute such as, consecutively, fuel quality, comfort, cleanness, personnel appearance, personnel performance and comfort.Keywords: gas station, fuel retail, Jakarta, competition, MDS, gap analysis, perceptual map, consumer perception.